Lymphatic Function in the Arms of Breast Cancer Patients—A Prospective Cohort Study. Issue 8 (August 2021) - Alstrup, Mathias; Johannessen, Andreas L.; Mohanakumar, Sheyanth; Offersen, Birgitte V.; Hjortdal, Vibeke E.
Abstract : Background: Lymphedema is a highly feared complication of breast cancer treatment, but the underlying complex mechanisms are still unknown. Thus, we investigated the lymphatic morphology and contractility in the lymphatic vessels of arms of high-risk breast cancer patients treated for node-positive early breast cancer. Methods: In this prospective cohort study 32 women treated for unilateral node-positive breast cancer were enrolled and studied 36 ± 23 days after loco-regional radiotherapy. Near-infrared fluorescence imaging was used to assess morphology and function of the superficial lymphatic vessels. Strain-gauge plethysmography was performed to evaluate the capillary filtration of fluid. Both arms were investigated, with the non-treated arm acting as control. The patients were questioned about the presence of lymphedema yearly and finally 574 ± 118 days after ended radiotherapy. Results: Morphologically, 25% of the treated arms expressed lymphatic vessel abnormalities compared to the control arms ( p = 0.0048). No difference in functional parameters (maximal pumping pressure, p = 0.20; contraction frequency, p = 0.63; contraction velocity, p = 0.55) was found between the treated and control arms. Patients who later developed lymphedema had a difference in velocity compared to those who did not develop lymphedema ( p = 0.02). The capillary filtration rate was similar between the two arms ( p = 0.18). Conclusions: Peripheral lymphatic vessels were morphologically changed in the ipsilateral arm in 25% of the patients and patients who later developed lymphedema showed an early increase in velocity. Other functional parameters and capillary filtration were unchanged in this early phase. These discrete changes might be early indicators of later development of lymphedema.